Dashboard untuk Memantau Kinerja Penjualan di Klinik Gustavet - Maulana, Aldi Resaldi; Tony, Tony (Computatio : Journal of Computer Science and Information Systems, 2024)
Gustavet Clinic is an animal acupuncture service that was specifically established in 1999 by Dr. Gustav. In 2006, Gustavet shifted its focus to holistic services, particularly animal acupuncture, under the guidance of Dr. Gustav, who personally studied acupuncture techniques from human acupuncture and established an acupuncture association in Indonesia along with his teachings. In 2012, Gustavet expanded into a veterinary and acupuncture clinic. The aim of this final project is to create an interactive dashboard using Tableau software, employing prototyping methods, to monitor sales at Gustavet Clinic. Data is extracted from sales records within the Kreloses inventory application, available at Gustavet Clinic, for the years 2021, 2022, and 2023. This dashboard provides an easy way to view information about pet food and veterinary drug sales. Through intuitive graphs and charts, users can quickly access information on total sales, profits, best-selling products, and year-over-year sales comparisons. The dashboard is designed to assist Gustavet Clinic in making better decisions to enhance sales performance and services for pet owners.